In Vivo Behavior of Revertants from Staphylococcus aureus L-Phase Variants Compared with the Parent Strain - Watanakunakorn, Chatrchai (1975)
The in vivo behavior of revertants of Staphylococcus aureus L-phase variants were studied in mice. The Giorgio strain of S. aureus was induced into L-phase variants by methicillin. After 13 serial passages in methicillin agar and six passages in antibiotic-free agar, reversion occurred. Six revertants, all phage untypable, coagulase negative, and mannitol negative, were inoculated intravenously into Swiss albino mice in comparison with the parent strain. Inoculation of 10(8) colony-forming units resulted in 38% mortality at 28 days for the Giorgio group and 0 to 2% for the revertants. The geometric mean titer of staphylococci in the kidneys was 3.5 × 10(5) for the Giorgio group and 0.5 × 10(0) to 1.0 × 10(2) for the revertants. Serial colony counts of blood, lungs, spleen, liver, and kidneys in mice inoculated with 10(7) colony-forming units showed faster clearance and failure of the revertant to colonize the kidneys. It is concluded that the in vivo behavior of the L-phase revertants was vastly different from that of the parent Giorgio strain.